Development and Optimization of Water-Soluble Double-Walled Carbon Nanotubes by Effective Surface Treatment of Inner Walls - Tewari, Chetna; Kim, Young Nam; Muramatsu, Hiroyuki; Endo, Morinobu; Kim, Yoong Ahm; Jung, Yong Chae (American Chemical Society, 2023)
Carbon nanotubes are a significant class of nanomaterials with distinctive properties that have led to their application in a variety of fields, such as polymer composites, medicine, electronics, and material science. However, their nonpolar nature and insolubility in polar solvents limit their applications. To address this issue, highly functionalized and water-soluble double-walled carbon nanotubes (DWNTs) were developed by selectively oxidizing the inner walls of the DWNTs using oleum and nitric acid. The impact of reaction time on the chemical functionalization of DWNTs was investigated under two different reaction durations of 2 and 24 h. The presence of highly oxygenated functional groups resulted in high water solubility, which was confirmed by high-and low-frequency Raman spectroscopy, high-resolution transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller (BET) method, and optical spectroscopy. The conductivity of highly water-soluble W-DWNTs (24 h) was 122.65 x 102 S cm-1. After annealing for 12 hat 140 degrees C, the W-DWNTs retained 72% of their conductivity (88.79 x 102 S cm-1).